(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: The present cross-sectional study examines the awareness and understanding of cancer of the esophagus in the general population in the Lakki Marwat and Bannu districts in Khyber Pakhtunkhwa, Pakistan. Purpose: To determine the amount of knowledge about esophageal cancer, its causative factors, and prevention methods. The presence of the disease was assessed with a structured questionnaire among 501 subjects, and it was shown that the degree of awareness was moderate since 62.3% of the subjects were aware of the disease. Results demonstrate the existence of significant gaps concerning the knowledge of dietary and lifestyle risk factors. It is interesting to note that tobacco consumption was identified as a potential risk factor by 77.6 per cent of the respondents. However, other prominent risks, like the use of hot beverages, have been recognized less. Demographic differences have also been brought out in the study, indicating that the young people and females are more aware. Conclusion: The findings demonstrate that there is an urgent need for a health education program intended explicitly for esophageal cancer awareness amongs the people. The interventions are significant as far as enhancing early detection and prevention programs are concerned, and eventually minimising the burden of the disease in these societies.